Analisis keterampilan berpikir kritis dalam pemecahan masalah matematika berdasarkan teori robert h ennis pada kelas v sekolah dasar - Annisa Fatiah; Riyadi Riyadi; Joko Daryanto (Didaktika Dwija Indria, 2021)
The purpose of this research is to analyze and characterize the critical thinking abality of 5th grade students at SD Negeri Mangkubumen Kidul No 16 Surakarta in the academic year 2020/2021 based on Robert H Ennis' theory to solve problems in distance, speed, and time material. In this research used method is descriptive qualitative with a case study approach. The data source of this study was students of grade 5Bth at SD Negeri Mangkubumen Kidul No 16 Surakarta, consisting of four children as research samples were taken by using a purposive sampling technique. Observation, interviewing, and document analysis were used to collect data, with data validity checking utilizing technique triangulation and time triangulation. The Miles and Huberman data analysis models were used to analyze the data. According to the findings of this study, students may identify the problem by meeting the two criteria. Students are well-equipped to create and assess problem-solving hypotheses since they only have one option for problem-solving, allowing them to meet one of the two markers. Because they have not been able to write problem-solving stages systematically, students are highly competent of applying the chosen problem-solving strategy. It may be inferred that the students failed to meet the indications for determining numerous different problem-solving strategies, and indicators of the problem-solving flow were methodically documented. Based on Robert Ennis’s theory the findings of this study provide insight into problem-solving abilities and serve as the foundation for additional research. The result of this research provide insight into critical thinking abilities based on Robert Ennis’s theory and orm the basis of the further research. This study's findings also motivate teachers to develop effective techniques, models, and ways to help pupils enhance their critical thinking skills.